Analysis of Swot Research Method in Developing Accounting Strategies - Karina, Hana; Oktavia, Nisa; Viasni, Sintia Ully; Nurulhuda, Siti Aisyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the use of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in the context of accounting strategy development. SWOT analysis is used to evaluate internal and external factors that influence the accounting practices of a business entity. Through collecting data from various sources, including analysis of financial reports and literature reviews, this research identifies internal strengths and weaknesses in the accounting system, as well as external opportunities and threats that may influence accounting strategies. The results of the SWOT analysis highlight specific advantages in the accounting system such as the efficiency of financial data management, the quality of human resources, and the technology used. On the other hand, weaknesses such as lack of system integration or limited resources are a major concern. From an external perspective, opportunities such as new technological developments or regulatory changes provide positive prospects, however, threats such as intense market competition or the risk of policy changes are challenges that must be overcome.